Cryptography, the Full Moon Festivals of Min, and the King: Reading the Cryptographic Inscription of the Chapel of Min in the Temple of Ramses II at Abydos - Lurson, Benoît.
In this paper, the author proposes a new reading of a cryptographic inscription engraved on the rear wall scene of Chapel XII in the temple of Ramses II at Abydos. According to this reading, which shows the importance of thematic cryptography for the conception of the inscription, a special form (xprw) of Min is said to go forth in procession at the occasion of the god’s second full moon festival. As a matter of fact, the crown worn by Min in the scene makes his depiction special, the iconographic program of the chapel refers to a procession, and the association of the god with the moon is well established. This inscription thus enables the reconstruction of twelve full moon festivals of Min, which in addition to the Festival of Min that was known to have taken place in I Shemu, were all celebrated with a procession.The iconographic program of Chapel XII also enables us to investigate the meaning of the full moon festival of Min. Royal ideology can be one level of meaning. Both in relation to the moon and its symbolism, the hypothesis of a celebration of Min as the divine father of the king can be put forward, whilst the takeover of the king might also have been in focus. Thus, this cryptographic inscription not only renews our knowledge of the New Kingdom theology and liturgy of Min, but also of the god’s importance for the royal ideology of the Ramesside Period.  doi: http://dx.doi.org/10.5913/jarce.53.2017.a011